1989
DOI: 10.1111/j.1365-2265.1989.tb00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lugol's Solution on Thyroid Function in Normals and Patients With Untreated Thyrotoxicosis

Abstract: Thirty-eight normal volunteers and 10 patients with untreated thyrotoxicosis were each given 0.5 ml of Lugol's solution daily for 10 days. On days 0, 5, 10, 15 and 20, serum levels of T4, free T4, T3 and TSH (by sensitive immunoradiometric assay) were measured. In normal subjects, the serum concentrations of free T4 declined significantly at day 10 while TSH levels were significantly increased at days 5, 10 and 15. Serum levels of T4 and T3 did not change significantly. All the observed changes took place with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Previous reports demonstrated that thyroid functions were suppressed in normal subjects following administration of drugs containing various amounts of iodine as follows: 0.25-1.5 mg as Na I [11], 0.42-3.8 mg as NaI [12], 12.5 mg as Lugol's solution [13], 27 mg as licorice lecithin-bound iodine [4], 114.8 mg as KI [14] per day. In the present study, 35 or 70 mg of iodine as 15 or 30 g of seaweed Kombu were administered daily, and the daily excretion of urinary iodine as iodide which is known to be the most valid index of absorbed iodine was estimated to be about 20 or 50 mg (57-71% of the iodine administered as Kombu).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrated that thyroid functions were suppressed in normal subjects following administration of drugs containing various amounts of iodine as follows: 0.25-1.5 mg as Na I [11], 0.42-3.8 mg as NaI [12], 12.5 mg as Lugol's solution [13], 27 mg as licorice lecithin-bound iodine [4], 114.8 mg as KI [14] per day. In the present study, 35 or 70 mg of iodine as 15 or 30 g of seaweed Kombu were administered daily, and the daily excretion of urinary iodine as iodide which is known to be the most valid index of absorbed iodine was estimated to be about 20 or 50 mg (57-71% of the iodine administered as Kombu).…”
Section: Discussionmentioning
confidence: 99%
“…One stayed euthyroid for 60 days, another showed a relative decrease in serum T4 and T3, which remained slightly elevated constantly for 60 days, a third case was lost to follow-up, and 6 cases relapsed. Tan et al (1989) observed in normal subjects no significant changes in serum T4 and T3, whereas free T4 was slightly but significantly decreased and TSH increased. The practical conclusions are that the physician should not be dogmatic about the use of iodides in hyperthyroidism.…”
Section: Discussionmentioning
confidence: 61%
“…The use of inorganic iodine for the preoperative preparation arid for thyrotoxic crisis is now firmly established, but, surprisingly, this treatment has not been studied adequately with modern techniques, in spite of a few studies, either short or with limited number of cases (Emerson et al, 1975;Roti et al, 1985;Tan et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In untreated hyperthyroidism 0.5 mL (375 mg) daily treatment with LS significantly reduces both free thyroxine (FT4) and free triiodothyronine (FT3) within 5–10 days, while TSH remains below the limit of detection (9). Aside from the effects on FT4 and FT3 levels, iodine also decreases the rate of blood flow, thyroid vascularity and intraoperative blood loss during thyroidectomy (10, 11).…”
Section: Introductionmentioning
confidence: 99%